The Succession of Bacterial Community Structure in Groundwater from a 250-m Gallery in the Horonobe Underground Research Laboratory. Issue 6 (3rd July 2017) - Ise, Kotaro; Sasaki, Yoshito; Amano, Yuki; Iwatsuki, Teruki; Nanjo, Isao; Asano, Takahiro; Yoshikawa, Hideki
ABSTRACT: We investigated the change in bacterial community structure after drilling boreholes, 09-V250-M02 and 09-V250-M03, in the 250-m deep research gallery of the Horonobe Underground Research Laboratory. In the 09-V250-M02 borehole, ϵ-Proteobacteria were predominantly detected in the clone library analyses of the groundwater samples conducted immediately after drilling. All the ϵ-Proteobacteria clones were closely related to Arcobacter spp ., which are known to be sulfide-oxidizing chemoautotrophic bacteria. After 4 years, the microbial structure drastically changed, and most detected operational taxonomic units were uncultured species such as candidate division OP9 and Chloroflexi relatives, which are frequently detected in deep sea sediments. The results indicated that the microbial community structure was drastically affected by borehole drilling and was concomitant with oxidation perturbation. However, these disturbed microbial communities changed within a few years to a microbial community composed of uncultivated species such as OP9 and Chloroflexi.